Influence of various factors on patient compliance after periodontal therapy: A pilot study - Rucha Shah; Raison Thomas; Shilpy Bhandari; Dhoom Singh Mehta (Wolters Kluwer Medknow Publications, 2017)
Background: Patient compliance is an important predictor of periodontal prognosis, therapy, and maintenance. Limited studies concentrate up on the factors which affect patient compliance. Thus, the aim of the study is to determine the relationship between sociodemographic data, patient's oral health awareness (OHA) and treatment satisfaction (TS) to patient compliance. Materials and Methods: A total of 150 patients were subjected to a prevalidated questionnaire comprising of thirty questions. Questions covered different aspects such as sociodemographic data, OHA, and level of patient TS. Statistical analysis was done using mean, percentages, and Spearman's correlation coefficient. Results: A sample of 150 people was included into the study of which 93 were females and 67 males with a mean age of 38 years. The total OHA scores when divided into three categories such as 5-7, 8-9, and> 10 and plotted against number of missed appointments; the difference found was statistically significant (P < 0.001). The mean TS was divided into four subgroups of score> 24, 25-27, 28-30, and> 31 and then plotted against the average number of missed appointments, and the difference was found to be statistically significant (P < 0.001). The correlation between the OHA score and number of missed appointments was −0.59 (P < 0.001) and TS score and number of missed appointments was −0.40 (P < 0.001). Conclusion: Within the limitations of the study, it can be concluded that patient education, OHA, and TS are the variables that influence the patient compliance.